1983
DOI: 10.1084/jem.158.3.901
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal IgM rheumatoid factors derived from arthritic MRL/Mp-lpr/lpr mice.

Abstract: MRL/lpr/lpr (MRL/l) mice develop a lupus-like syndrome and a disease histologically and serologically similar to human rheumatoid arthritis. Their sera contain polyclonal IgM rheumatoid factors (RF) reactive with all murine IgG subclasses (frequently strongest with IgG2a) and several heterologous IgG. To examine the repertoire and epitopic specificities of these RF, we fused splenocytes from 3.5-mo-old seropositive MRL/l mice with appropriate myeloma partners and derived 1,723 hybridomas of which 23 secreted I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1984
1984
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…ihc failure to form RF with the cryoglobulin activity may partly account for the development of only mild tissue lesions in B6andC3H mice bearing the/pr or ^/(/mutation [10.30]. It has been shown thai IgM RFMn MRL-lpr m\cc had higher reactivity to IgG2a, white IgM RI" from B6-and C3H-//J;' mice reacted better with IgGI [24,27,28]. However, in our present study, the RF .specificity to murine IgG subclasses did not differ markedly among Ihc three Ipr strains of mice, although the C3H'gld mice had a tendency to exhibit relatively higher activities of anli-IgGl RF.…”
Section: Discussionmentioning
confidence: 99%
“…ihc failure to form RF with the cryoglobulin activity may partly account for the development of only mild tissue lesions in B6andC3H mice bearing the/pr or ^/(/mutation [10.30]. It has been shown thai IgM RFMn MRL-lpr m\cc had higher reactivity to IgG2a, white IgM RI" from B6-and C3H-//J;' mice reacted better with IgGI [24,27,28]. However, in our present study, the RF .specificity to murine IgG subclasses did not differ markedly among Ihc three Ipr strains of mice, although the C3H'gld mice had a tendency to exhibit relatively higher activities of anli-IgGl RF.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that IgM RF can be formed spontaneously [1] and following mitogenic or antigenic stimulation in non-autoimmune strains of mice [2][3][4]. RF formed in non-autoimmune mice are nearly always restricted to the IgM class, while lupusprone MRL-lpr/lpr mice deficient in the Fas apoptosis receptor spontaneously produce high titers of IgG RF as well as IgM RF [5][6][7]. Circulating intermediate-sized immune complexes (IC) consisting of IgG RF [8,9], similar to those found in sera or synovial fluids from patients with rheumatoid arthritis [10], could contribute to several pathological manifestations, such as necrotizing arteritis and arthritis, uniquely observed in MRL-lpr/lpr mice [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, using diVerent batches of RF preparations, the IC ELISAs were diYcult to standardize. HMABs speciWc for RF might represent an alternative, even though there may be problems of availability [8,20].…”
Section: Discussionmentioning
confidence: 99%